SIRT1 mediated gastric cancer progression under glucose deprivation through the FoxO1-Rab7-autophagy axis - Zhu, Mengke; Wei, Chao; Wang, Haijiang; Han, Shangning; Cai, Lindi; Li, Xiaowen; Liao, Xinhua; Che, Xiangming; Li, Xuqi; Fan, Lin; Qiu, Guanglin (Frontiers in Oncology, 2023)
Purpose: Silent mating type information regulator 2 homolog 1 (SIRT1) and autophagy have a two-way action (promoting cell death or survival) on the progression and treatment of gastric cancer (GC) under different conditions or environments. This study aimed to investigate the effects and underlying mechanism of SIRT1 on autophagy and the malignant biological behavior of GC cells under conditions of glucose deprivation (GD). Materials and methods: Human immortalized gastric mucosal cell GES-1 and GC cell lines SGC-7901, BGC-823, MKN-45 and MKN-28 were utilized. A sugar-free or low-sugar (glucose concentration, 2.5 mmol/L) DMEM medium was used to simulate GD. Additionally, CCK8, colony formation, scratches, transwell, siRNA interference, mRFP-GFP-LC3 adenovirus infection, flow cytometry and western blot assays were performed to investigate the role of SIRT1 in autophagy and malignant biological behaviors (proliferation, migration, invasion, apoptosis and cell cycle) of GC under GD and the underlying mechanism. Results: SGC-7901 cells had the longest tolerance time to GD culture conditions, which had the highest expression of SIRT1 protein and the level of basal autophagy. With the extension of GD time, the autophagy activity in SGC-7901 cells also increased. Under GD conditions, we found a close relationship between SIRT1, FoxO1 and Rab7 in SGC-7901 cells. SIRT1 regulated the activity of FoxO1 and upregulated the expression of Rab7 through deacetylation, which ultimately affected autophagy in GC cells. In addition, changing the expression of FoxO1 provided feedback on the expression of SIRT1 in the cell. Reducing SIRT1, FoxO1 or Rab7 expression significantly inhibited the autophagy levels of GC cells under GD conditions, decreased the tolerance of GC cells to GD, enhanced the inhibition of GD in GC cell proliferation, migration and invasion and increased apoptosis induced by GD. Conclusion: The SIRT1-FoxO1-Rab7 pathway is crucial for the autophagy and malignant biological behaviors of GC cells under GD conditions, which could be a new target for the treatment of GC.